2012
DOI: 10.1590/s1980-65742012000300008
|View full text |Cite
|
Sign up to set email alerts
|

Análise da técnica de pedalada durante o ciclismo até a exaustão

Abstract: O objetivo deste estudo foi verificar a influência da fadiga na técnica de pedalada durante teste de ciclismo máximo até a exaustão. Oito ciclistas treinados realizaram um teste incremental máximo e um teste de carga constante até a exaustão com 48 horas de intervalo. As forças resultante (FR) e efetiva (FE) aplicadas no pedal foram calculadas para a determinação do índice de efetividade (IE). A FE apresentou aumento entre o início e fim do teste (de 125 ± 16 para 169 ± 52 N, p=0,03), enquanto o IE e a FR não … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…There was also an increase in torque resulting from the hip and knee joints at the end of the test, as a cyclists' strategy to maintain performance. Furthermore, Diefenthaeler et al (2012a) observed that IE did not show significant pedal force changes, indicating a pedaling technical maintenance of the applied pedal force, possibly as a strategy to maintain the workload during high intensity cycling. Changes in muscle recruitment caused by the onset of fatigue processes may generate changes in the capacity to produce force during crank cycle, possibly explaining these results (Dorel et al, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…There was also an increase in torque resulting from the hip and knee joints at the end of the test, as a cyclists' strategy to maintain performance. Furthermore, Diefenthaeler et al (2012a) observed that IE did not show significant pedal force changes, indicating a pedaling technical maintenance of the applied pedal force, possibly as a strategy to maintain the workload during high intensity cycling. Changes in muscle recruitment caused by the onset of fatigue processes may generate changes in the capacity to produce force during crank cycle, possibly explaining these results (Dorel et al, 2009).…”
Section: Discussionmentioning
confidence: 93%